1998
DOI: 10.4141/s97-069
|View full text |Cite
|
Sign up to set email alerts
|

Selenium concentration in plant material, drainage and surface water as influenced by Se applied to barley foliage in a barley – red clover – potato rotation

Abstract: . 1998. Selenium concentration in plant material, drainage and surface water as influenced by Se applied to barley foliage in a barley -red clover -potato rotation. Can. J. Soil Sci. 78: 685-688. Foliar application to barley of 10 and 20 g Se ha -1 , as sodium selenate, increased Se content of barley grain and straw and red clover forage. There was no significant effect of Se application on Se content of potato petioles or tubers in the third year of the rotation. The Se content of drainage water was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Foliar application to barley at 10 and 20 g Se ha -1 , as sodium selenate, increases the Se contents of barley grain (MacLeod et al, 1998). Morever, a stimulatory effect of foliar application of Se on nitrogen assimilation has been reported for barley (Aslam et al, 1990), however, there is few published work concerning the expression of selenium effects on dry matter accumulation, protection against the oxidative stress and regulation the water status of Hordeum vulgare L. (barley).…”
Section: Introductionmentioning
confidence: 99%
“…Foliar application to barley at 10 and 20 g Se ha -1 , as sodium selenate, increases the Se contents of barley grain (MacLeod et al, 1998). Morever, a stimulatory effect of foliar application of Se on nitrogen assimilation has been reported for barley (Aslam et al, 1990), however, there is few published work concerning the expression of selenium effects on dry matter accumulation, protection against the oxidative stress and regulation the water status of Hordeum vulgare L. (barley).…”
Section: Introductionmentioning
confidence: 99%
“…Application of Se at up to 50 g Se ha -1 or higher should not pose any toxic effect in water or to the bird or aquatic life. MacLeod et al (1998), in a study on a fine sandy loam soil, reported that a rate of 20 g Se ha -1 produced Se levels in ground water which were 40 to 100 times less than levels considered toxic. Therefore, doubling the For personal use only.…”
mentioning
confidence: 98%
“…Foliar application of Se in the form of Na 2 SeO 3 under various crops is stated by MacLeod et al (1998) and Cao et al (2001). Differences between essential and toxic rates of Se are very narrow (Tan et al 2002, Fargašová 2004, Fargašová et al 2006.…”
mentioning
confidence: 99%